RNA-Binding Profiles of CKAP4 as an RNA-Binding Protein in Myocardial Tissues - Zhu, Hong; Zhang, Yanfeng; Zhang, Chengliang; Xie, Zhongshang (Frontiers in Cardiovascular Medicine, 2021)
Background: Pathological tissue remodeling such as fibrosis is developed in various cardiac diseases. As one of cardiac activated-myofibroblast protein markers, CKAP4 may be involved in this process and the mechanisms have not been explored. Methods: We assumed that CKAP4 hold a role in the regulation of cardiac fibrotic remodeling as an RNA-binding protein. Using improved RNA immunoprecipitation and sequencing (iRIP-seq), we sought to analyze the RNAs bound by CKAP4 in normal atrial muscle (IP1 group) and remodeling fibrotic atrial muscle (IP2 group) from patients with cardiac valvular disease. Quantitative PCR and Western blotting were applied to identify CKAP4 mRNA and protein expression levels in human right atrium samples. Results: iRIP-seq was successfully performed, CKAP4-bound RNAs were characterized. By statistically analyzing the distribution of binding peaks in various regions on the reference human genome, we found that the reads of IP samples were mainly distributed in the intergenic and intron regions implying that CKAP4 is more inclined to combine non-coding RNAs. There were 913 overlapping binding peaks between the IP1 and IP2 groups. The top five binding motifs were obtained by HOMER, in which GGGAU was the binding sequence that appeared simultaneously in both IP groups. Binding peak-related gene cluster enrichment analysis demonstrated these genes were mainly involved in biological processes such as signal transduction, protein phosphorylation, axonal guidance, and cell connection. The signal pathways ranking most varied in the IP2 group compared to the IP1 group were relating to mitotic cell cycle, protein ubiquitination and nerve growth factor receptors. More impressively, peak analysis revealed the LncRNA-binding features of CKAP4 in both IP groups. Furthermore, qPCR verified CKAP4 differentially bound LncRNAs including LINC00504, FLJ22447, RP11-326N17.2 and HELLPAR in remodeling myocardial tissues when compared with normal myocardial tissues. Finally, the expression of CKAP4 is down-regulated in human remodeling fibrosic atrium. Conclusions: We reveal certain RNA-binding features of CKAP4 suggesting a relevant role as an unconventional RNA-binding protein in cardiac remodeling process. Deeper structural and functional analysis will be helpful to enrich the regulatory network of cardiac remodeling and to identify potential therapeutic targets.